The Association between Limited English Proficiency and Sepsis Mortality. Issue 3 (20th November 2019) - Jacobs, Zachary G; Prasad, Priya A; Fang, Margaret C; Abe‐Jones, Yumiko; Kangelaris, Kirsten N
Abstract : BACKGROUND: Limited English proficiency (LEP) has been implicated in poor health outcomes. Sepsis is a frequently fatal syndrome that is commonly encountered in hospital medicine. The impact of LEP on sepsis mortality is not currently known. OBJECTIVE: To determine the association between LEP and sepsis mortality. DESIGN: Retrospective cohort study. SETTING: 800‐bed, tertiary care, academic medical center. PATIENTS: Electronic health record data were obtained for adults admitted to the hospital with sepsis between June 1, 2012 and December 31, 2016. MEASUREMENTS: The primary predictor was LEP. Patients were defined as having LEP if their self‐reported primary language was anything other than English and interpreter services were required during hospitalization. The primary outcome was inpatient mortality. Mortality was compared across races stratified by LEP using chi‐squared tests of significance. Bivariable and multivariable logistic regressions were performed to investigate the association between mortality, race, and LEP, adjusting for baseline characteristics, comorbidities, and illness severity. RESULTS: Among 8, 974 patients with sepsis, we found that 1 in 5 had LEP, 62% of whom were Asian. LEP was highly associated with death across all races except those identifying as Black and Latino. LEP was associated with a 31% increased odds of mortality after adjusting for illness severity, comorbidities, and other baseline characteristics, including race (OR 1.31, 95% CI 1.06‐1.63, P = .02). CONCLUSIONS: In a single‐center study of patients hospitalized with sepsis, LEP was associated with mortality across nearly all races. This is a novel finding that will require further exploration into the causal nature of this association. Abstract :